PENGARUH MOTIVASI TERHADAP MINAT BERINVESTASI DI PASAR MODAL DENGAN PEMAHAMAN INVESTASI DAN USIA SEBAGAI VARIABEL MODERATE - Situmorang, Masri; Natariasari, Riska; ', Andreas (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study purpose is to examined if knowledge investment and age afford to moderate the effect of motivation towards investment interest in stock market. Which is the motivation consist of subvariabel social, self appreciation dan self actuality. Population of this research are the real investor in Pekanbaru. Sampling method is used random sampling.Data collected method used questionnaire which is spreaded to 86 respondent of investor in Pekanbaru. The hypotesis is examined by multiple linier regression and moderated regression analysis (MRA). And this research has results. First, investment knowledge has afford to moderate the effect of social motivation towards investment interest. Second, age has afford to moderate the effect of social motivation towards investment interest in Stock Market.Keywords : Motivation, Investment Interest, Investment Knowledge and Age.